Colored Quark and Colored Gluon in Standard Model, Hadronic Constituents (Global Journal of Science Frontier Research, 2023)
In current particle physics Color of aparticle and Spin of this particle belong to different space and researchs on hadronic constituents are going under this guidance In this paper base on color representation of flavor t c u d s b of quarks and their antiquarks color and spin are postulated to be combined into a common space STS In this space quark and gluon can be turned into colored quark and colored gluon directly by being colored with quark colors qR qG qB and antiquark colors qR qG qB Along with such idea of hadronic constituents Consequently we have For observed baryon constituent colored baryon particle and force-mediating coloredgluon particle For observed meson constituent colored meson particle and force-mediating colored gluon particle The above process of the color role related to hadronic constituents in this paper are much different from that of current SU 3 color And total spin S3 qqq qqqcolor of colored baryon couldbe one-third series And total spin S3 qq qqcolor of colored meson couldbezero integer evenhalf-integer Although the phenomenons of such S3 may not beobserved Colored pseudoscalar meson and colored vector meson separately are singlet and triplet ofspin-colorstate qq when colored gluons occupy color ground state 0 0 Colored scalar meson and colored pseudo vector meson separately are singlet and triplet of spin-color state qq when colored gluons transfer to color excited state 1 2 1 2 0 The above introduction of gluon color ground state 0 0 and gluon corlor excited state 1 2 instead of orbital angular momentums L 0 and L 1 of quarks in current theory Possible new flovors X1 X2 X3 and Y1 Y2 Y3 are incidental to this paper Multi quark hadrons constituents may refer this paper work too
Keywords: quarkcolor; guloncolor; coloredquark; coloredgluon; gluoncorlormatrix; spin-colorstate